Gas Sensing Properties of bis-Phthalocanine Thin Film - (:unkn) unknown (AMER INST PHYSICS, 2009)
In this study, response of the cofacial bis-phthalocyanine film to vapor of Volatile Organic Compounds (VOCs) was investigated. Test gases were vapors of acetone, toluene, ethanol and ammonia. Measurements were carried out between the temperatures of 293 K 423 K. Bis-phthalocyanine was dissolved in chloroform. Thin film of bis-phthalocyanine was deposited by spraying method on glass substrate patterned with Interdigital Transducer (IDT). During the measurements 0.5 volts were applied to the IDT Response characteristics of the film were determined by means of change in dc conductivity as a function of gas concentration and temperature. Gas concentrations were controlled by mass flow controller. Dry nitrogen was used as carrier gas. Vapor pressure of the VOCs was calculated using Antoine equation. Response characteristics of the film were determined in a wide range of gas concentration (0.25%-18%). The film showed good sensitivity to the VOCs vapors in the measurement range. The responses of the film were reversible All the measurement system was computerized
Keywords: Phthalocyanine; sensor; VOC; thin film; PHTHALOCYANINES; ZINC(II); MACROCYCLES